Jacobsen syndrome without thrombocytopenia: a case report and review of the literature - Nalbantoğlu, Burçin; Donma, M. Metin; Nişli, Kemal; Paketçi, Cem; Karasu, Erkut; Özdilek, Burcu; Mintaş, Nuriye Ece (The Turkish Journal of Pediatrics, 2013)
Jacobsen syndrome (JS), a rare disorder with multiple dysmorphic features, is caused by the terminal deletion of chromosome 11q. Typical features include mild to moderate psychomotor retardation, trigonocephaly, facial dysmorphism, cardiac defects, and thrombocytopenia, though none of these features are invariably present. The estimated occurrence of JS is about 1/100,000 births. The female/male ratio is 2:1. The patient admitted to our clinic at 3.5 years of age with a cardiac murmur and facial anomalies. Facial anomalies included trigonocephaly with bulging forehead, hypertelorism, telecanthus, downward slanting palpebral fissures, and a carp-shaped mouth. The patient also had strabismus. An echocardiogram demonstrated perimembranous aneurysmatic ventricular septal defect and a secundum atrial defect. The patient was